Psychometric properties and measurement invariance across gender of the Italian version of the tempest self-regulation questionnaire for eating adapted for young adults - Diotaiuti, Pierluigi; Girelli, Laura; Mancone, Stefania; Valente, Giuseppe; Bellizzi, Fernando; Misiti, Francesco; Cavicchiolo, Elisa (Frontiers in Psychology, 2022)
The prevalence of overweight and obesity in young adults has increased dramatically in recent decades. The unhealthy eating habits that develop at this time can often lead to negative health consequences in the future. It is therefore important to learn about self-regulation and self-control strategies and help young adults to have healthy eating behaviours. This study aims to present an Italian version of the TESQ-E tool adapted for young adults. The instrument assesses self-regulation and self-control strategies to counteract the desire and temptation to eat unhealthy food and to choose healthy foods. A total of 645 students (271 males and 374 females with an average age of 24.82 and SD = 4.34) took part in the study. The 20-item model demonstrated a good fit to the data, showing six specific self-regulation strategies loading on three general self-regulation approaches (addressing the temptation directly, addressing the psychological meaning of temptation, addressing the goal directly) which represented one higher-order factor, the self-regulatory competence. The results of the confirmatory factor analysis (CFA) provided support for the posited model for the TESQ-E: χ2 (152) = 336.480, p < 0.001; CFI = 0.95; RMSEA = 0.04; SRMR = 0.04. The third-order factor structure of the scale showed full measurement invariance across gender. The analysis also showed that females appear to prefer strategies that directly address the goal by expressing explicit intentions or plans to eat in a healthy way. Convergence validity was tested through correlations with ESEBS (Eating-Self-Efficacy Brief Scale), EES (Emotional Eating Scale), SAHE (Scale of Attitudes towards Healthy Eating) and BMI. The scale has demonstrated to be a reliable instrument with the good psychometric properties that can be easily used with young adults to measure self-regulation strategies in eating in order to plan personalised interventions for the prevention and control of the metabolic syndrome.